Benefits and risks of cannabis cosmetics for free sale in Colombia - Rodríguez Castro, Dorys Yaneth
Numerous benefits for the skin are attributed to Cannabis sativa creating an uprisal of cosmetics that include it in their formula.This paper aims to evaluate some over-the-counter cannabis cosmetics in the Colombian market, looking forward to answer if those are recommended for dermocosmetic use. In order to accomplish this objective, there was a systematic review conducted of the ingredients and characteristics of 98 cannabis cosmetics with valid sanitary disclaimer in the country. This review showed that most (90%) of the cannabis cosmetics available in Colombia are produced inside the country. 44% of the evaluated products include CBD in their formula, 35% use hemp seed extract, while 11% combine those ingredients in some way.The analysis of the ingredients revealed several weaknesses in the composition of the cannabis cosmetics evaluated that limit their dermocosmetic use. In some cases, the ingredients included represent risks for the skin’s health. The results from this review lead to conclude that cannabis cosmetics sold in the country do not have efficacy or safety tests to ensure their dermocosmetic use or many of the effects claimed on their labels. Due to the number of cannabis cosmetics sold over the counter, it is recommended that consumers verify if the products have any clinical evidence that supports their dermocosmetic use.